Risk Factors of Acute Upper Respiratory Tract Infection Incidence (Non-Covid-19): A Case Study in the Work Area of the Sukorejo Primary Healthcare Center, Pacitan Regency - Nurtanti, Ratna; Azam, Mahalul (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2022)
Introduction: Acute Upper respiratory tract infection was the highest case among the other diseases in Sukorejo Primary Healthcare Center, Pacitan Regency. Health protocol policies have an impact on healthy living behavior, which can prevent COVID-19 and acute upper respiratory infection (non-COVID-19). Rumors in the community stated that all acute upper respiratory infections had been tested for COVID-19, and were declared positive for COVID-19. This study aimed to determine the factors associated with acute upper respiratory tract infections (non-COVID-19).Methods: This study was conducted in an analytic observational method with a case-control study design. There were 61 subjects in the case and 61 subjects aged 26-65 years in the control groups. Sampling was done by simple random sampling for the case and purposive sampling for the control group. Data were analyzed by chi-square tests and logistic regression models.Results: Based on bivariate analysis, the inappropriate use of masks, smoking, inappropriate hand washing habits, high density on room occupancy, and inappropriate house ventilation area were the risk factors of acute upper respiratory tract infections (non-COVID-19). After controlling for the other variables, smoking habits (OR=2.723; 95%Cl=1.216-6.098; p=0.015), inappropriate house ventilation area (OR=2.569; 95%Cl=1.149-5.743; p=0.022), high density in room occupancy density (OR=2.425; 95%Cl=1.087-5.410; p =0.031) and the inappropriate use of masks (OR=2.320; 95%Cl=1.021-5.173; p=0.045) were the risk factors of acute upper respiratory tract infection (non-COVID-19) incidence.Conclusion: The risk factors of acute upper respiratory tract infection (non-COVID-19) incidence were smoking habits, inappropriate house ventilation, high density in room occupancy and the inappropriate use of masks